Validação e aplicação de método para determinação de metabólitos microalgais empregando cromatografia em fase gasosa - Vendruscolo, Raquel Guidetti (2016)
The study of metabolism through the metabolites determination is assuming great importance in biological scientific scene, once it allows the knowledge or even understanding of how and why they are modified by existing routes in biological matrices. Microalgae are unicellular organisms prokaryotes or eukaryotes with photosynthetic capacity, that presents relatively simple requirements for growth and high potential to technological interest products synthesis. Thus, the aim of this study was to develop a simultaneous extraction method of non-polar fraction (fatty acids) and polar (amino acids and organic acids) in microalgae intracellular content, employing gas chromatography (GC) as analytical analysis tool. The compounds were extracted by Bligh e Dyer method with reducing the volume organic solvents and different forms of agitation and/or cell disruption. The non-polar compounds were derivatizated by Hatman e Lago method. The derivatization of polar compounds was performed according to Oms-oliu and validated for microalgae biomass sample, considering selectivity, linearity, detection and quantification limits, precision and accuracy. Then, were analyzed two chlorophytes, Chlorella vulgaris and Scenedesmus obliquus and two cyanobacteria, Aphanothece microscopica Nägeli and Phormidium autumnale. Eleven fatty acids, ten amino acids and three organic acids were detected between the species. The succinic, malic and citric acids, important intermediates from tricarboxylic acid cycle (TCA), from which are formed microalgae products of interest. Among the amino acids, the glutamic acid was the major compound in all species. Excepting the S. obliquus, the microalgae showed fatty acid profile mostly with saturated carbon chain. Posteriorly, the organic acids, amino acids and fatty acids were characterized during growth of S. obliquus microalgae cultivated photosynthetically with constant lighting. The succinic acid showed constant concentrations after 120 h of cultivation, while malic and citric acids had a significantly higher concentration to 336 h. Excepting the alanine, glutamic acid and asparagine, which showed peak in 336 h, the highest concentrations of amino acids were observed between 120 and 288 h. The fatty acid profile showed significant change between analysis of 0 to 120 h. Firstly the cultivation was characterized by the high concentration of saturated FA and short and medium chain compounds. After 120 h was detected higher concentration of unsaturated AG and long-chain (≥ 20 carbons). In this regard, it was possible establish relationship between microalgae biosynthetic pathways.